BEMPEDOIC ACID (ETC-1002) AS A NEW ALTERNATIVE TO STATIN THERAPY: AN UPDATED META-ANALYSIS AND SYSTEMATIC REVIEW WITH GRADE APPROACH - Paulus, Ivana Beatrice; Semadi, I Made; Nugraha, Ida Bagus Aditya; Suastika, Ketut (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Bempedoic acid inhibits ATP-citrate lyase (ACL) two steps upstream of HMG-CoA reductase and may be recommended for patients who have not achieved LDL-C targets despite maximally tolerated or high-intensity statin therapy. Until now, there is no meta-analysis performed and this study intends to answer this question and to provide additional trials. METHODOLOGY Studies were searched using keywords: Bempedoic Acid or ETC-1002 and lipid in several databases of the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, ScienceDirect, and OVID. All references were reviewed using the Centre for Evidence-Based Medicine critical appraisal checklist. The descriptions of the extracted data are guided by the Preferred Reporting Items for Systematic Reviews (PRISMA) statement with GRADE approach. 4385 papers were initially collected, and twelve studies were pooled and entered review synthesis. RESULTS Ten RCTs were identified with a total of 3754 patients, 2468 intervention and 1284 control, and followed up for 4 to 52 weeks. The combined data showed that the primary endpoint, percent changes in LDL-C MD -25.81 [95 CI% -29.56, -22.06], was statically significant. Secondary endpoints were to assess the percent change from baseline for non-HDL-C -20.19 [95 CI% -23.42, -16.95] and apolipoprotein B -15.43 [95 CI% -17.09, -13.76] with a p value of <0.00. Two studies revealed that when adding it to dual therapy, 90% of patients achieved LDL-C <70 mg/dL, and 95% of patients had ≥50% lower LDL-C from baseline to week 6;. One study showed that adding PCSK9i lowered LDL-C by 30.3% vs placebo (P<.001). CONCLUSION Bempedoic acid significantly decreased LDL-C, non-HDL-C, and apolipoprotein B levels.